2019
DOI: 10.9734/ajrimps/2019/v7i130113
|View full text |Cite
|
Sign up to set email alerts
|

Pyridinium Crosslinks (Pyd) in the Urine is Associated with Stunting in Neonates

Abstract: Aims:The aim of the research is to evaluate the reliability of bone resorption biomarkers called Pyridinium Crosslinks (Pyd) in the urine of the neonates as an evaluation to bone growth of the neonate, as an indicator of stunting. Study Design: A cross-sectional study. Place and Duration of Study: Andini Mothers and Children Hospital (Pekanbaru, Indonesia). Duration of the study was between, August until September 2014. Methodology: Subjects of study were 35 healthy neonates. Subjects were recruited at the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
1
2
Order By: Relevance
“…Besides, the current finding is higher when compared to other study conducted in Indonesia, 22.9% [49]. The economic discrepancy among the two nations could explain the observed difference although income was not associated with stunting in the current study, it's been well-established that it greatly affects the nutritional status [49]. To put simply, the Indonesian's GDP per Capita is estimated to be 4042.662 billion USD, which is higher than Ethiopian GDP Per Capita which is, 1,122.5141 USD) [50].…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Besides, the current finding is higher when compared to other study conducted in Indonesia, 22.9% [49]. The economic discrepancy among the two nations could explain the observed difference although income was not associated with stunting in the current study, it's been well-established that it greatly affects the nutritional status [49]. To put simply, the Indonesian's GDP per Capita is estimated to be 4042.662 billion USD, which is higher than Ethiopian GDP Per Capita which is, 1,122.5141 USD) [50].…”
Section: Discussioncontrasting
confidence: 76%
“…It's utterly known that good maternal nutritional status reduces the likelihood of neonatal stunting [48]. Besides, the current finding is higher when compared to other study conducted in Indonesia, 22.9% [49]. The economic discrepancy among the two nations could explain the observed difference although income was not associated with stunting in the current study, it's been well-established that it greatly affects the nutritional status [49].…”
Section: Discussioncontrasting
confidence: 53%
“…The prevalence of short-birth babies in this study was 19.4%. Previous research in Indonesia showed higher prevalence results, 23.4% and 22.9%, respectively 13,14 . Different results are possible because previous studies were taken in 2017 and 2019.…”
Section: Resultsmentioning
confidence: 78%